Pengaruh Ketaatan Aturan Akuntansi, Efektivitas Pengendalian Internal, dan Sifat Love of Money Terhadap Kecenderungan Kecurangan Akuntansi - Lisda Nursanti; Tumirin Tumirin (Universitas Muhammadiyah Gresik, 2022)
This study aims to examine the effect of compliance with accounting rules, the effectiveness of internal control, and the nature of love of money on the tendency of accounting fraud. This type of research is a quantitative research. The sample of this research is village officials who work in the financial management department which consist of the Village Head, Village Secretary, Finance Head, and Planning Head in Manyar District and Kebomas District, Gresik Regency. The technique used in this research is purposive sampling and obtained a sample of 100 respondents. The data used in this study is primary data in the form of a questionnaire. The analytical technique used is multiple linear regression analysis with SPSS version 25.0 program. The results showed that the variables of accounting rule compliance and the effectiveness of internal control had a negative and significant effect on the tendency of accounting fraud. While the nature of love of money has a positive and significant effect on the tendency of accounting fraud.